PERAN METODE DISKUSI, PEMBERIAN TUGAS DAN MOTIVASI BELAJAR TERHADAP PENCAPAIAN LULUSAN PESERTA DIDIK DI SMP NEGERI I OMBEN KABUPATEN SAMPANG - Syafril Effendy; Subijanto; Fatimah Riswati (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 34 teachers. The objectives of this study are 1). Does the method of discussion, assignment and learning motivation simultaneously have a significant influence on the achievement of students' graduates at SMP Negeri I Omben, Sampang Regency. 2.) Does the method of discussion, assignment and learning motivation partially have a significant effect on the achievement of students' graduates at SMP Negeri I Omben, Sampang Regency. 3.) Which variable between the method of discussion, assignment and learning motivation has a dominant influence on the achievement of student graduates in SMP Negeri I Omben, Sampang Regency. The results showed that 1.) The method of discussion, assignment and learning motivation simultaneously had a significant influence on the achievement of students' graduates at SMP Negeri I Omben, Sampang Regency. 2.) The method of discussion, assignment and learning motivation partially has a significant influence on the achievement of students' graduates at SMP Negeri I Omben, Sampang Regency. 3.) Learning motivation has a dominant influence on the achievement of students' graduates at SMP Negeri I Omben, Sampang Regency